Chapter Fostering Critical Reflection in The Frame of Transformative Learning in Adult Education: Italian and Nigerian Comparative Case Studies - Tajudeen Ade, Akinsooto (Studies on Adult Learning and Education, 2020)
Critical reflection (CR) is an important process for making decisions on complex issues that influence individuals and societal life. The ability to inform our perceptions and thoughts through the results of critical reflection on our assumptions is fundamentally important in order to face the challenges connected to adult life (Kreber, 2012). Under the perspective of transformative learning (Mezirow & Associates, 2000), the paper discusses the similarities and differences between the ways in which the Italian and Nigerian higher education systems support students' critical reflection. The results show how the two systems are on the right track to implementing the process at the micro and meso levels.